Exploratory behavior, but not aggressiveness, is correlated with breeding dispersal propensity in the highly philopatric thorn-tailed rayadito - Botero Delgadillo, Esteban.; Quirici, Verónica; Poblete Quintanilla, Yanina.; Poulin, Elie; Kempenaers, Bart; Vásquez, Rodrigo A. (Wiley, 2020)
Studies on the relationship between behavioral traits and dispersal are necessary to understand the evolution of dispersal syndromes. Empirical studies have mainly focused on natal dispersal, even though behavioral differences between dispersers and philopatric individuals are suspected to hold through the whole life cycle, potentially affecting breeding dispersal propensity. Using capture–mark–recapture data and behavioral trials in a forest passerine, the thorn-tailed rayadito Aphrastura spinicauda, we describe inter-individual differences in exploratory behavior and aggressiveness, and investigate the relationship between those traits and breeding dispersal. Our study took place in Fray Jorge National Park, north-central Chile, where a relatively isolated population of rayaditos inhabits a naturally fragmented environment. We found that scores for behavioral traits were consistent between years. Exploratory behavior was similar between sexes, while males showed higher levels of aggression towards a conspecific male intruder. Only exploratory behavior was related to breeding dispersal propensity, with fast-exploring rayaditos being more likely to have dispersed between seasons. This finding provides indirect evidence for the existence of a dispersal strategy that could reduce dispersal costs in the fragmented landscape of Fray Jorge. To our knowledge, this is the first study documenting an association between breeding dispersal and exploratory behavior in a wild bird population. A longitudinal individual-based study will help determining whether this association constitutes a behavioral syndrome.
Keywords: Behavioral traits.; Breeding dispersal.; Chile.; Dispersal syndromes; Furnariidae.